Semiotic Analysis of the Tortor Dance in North Sumatran Wedding Ceremonies - Indriana Octavita, Rr. Astri; Ika Yuliana, Tiarma; Novia Ulfa, Rima; Ghufron, M. Ali (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2024)
This research intends to investigate the meaning contained behind the Tor-Tor dance. The researcher intends to use theories in this research, namely semiotic theory, nonverbal communication theory, and dance. The purpose of this research is to find out the meaning contained in the clothes and accessories used, song lyrics, and the meaning of each Tor-Tor Huda-Huda dance movement. The research method used in this research is an interpretive approach using Roland Barthes' semiotic analysis. Researchers collected data in the form of observations and secondary data in the form of journals, articles on the internet that support this research. The reason, why researchers are interested in it, is because dance is not only a means of expression but as a means of communication to express and express, commenting on the reality of life through dance movements. As a means of communication, dance through space-time movement carries a certain mission or message to be understood by the audience, while the body is the dancer's tool for communication. So the success or failure of communication through dance is also determined by the dancer's movements in each movement. For this reason, this research is considered important because of the diversity of meanings.